Evolution of the Dead Sea brine during the last glacial cycle from chemical compositions of interstitial soluble salts in sedimentary sections - Omri Khalifa; Mordechai Stein; Amitai Katz; Boaz Lazar (PANGAEA, 2025)
This data set provides temporal variations in the Na/Cl, Mg/Cl, Br/Cl, and Br/Mg ratios of the deep (hypolimnion) and the overlying (epilimnion) brines of Lake Lisan that filled the Dead Sea Basin between ~100-13 ka period were retrieved from soluble salts within the lake extquotesingles sediments. The soluble salts were extracted from cores drilled in the Dead Sea deep and shallow DSDDP cores numbers 5017-1-A and 5017-3-C, respectively, and from the Marginal outcrops of the Lisan Fm. exposed in the Perazim Valley (section PZ-1) and the White Hill (section GL-1). The ages from cores 5017-1-A and the marginal exposure of the White Hill section GL-1 were calculated using the relevant Time-Depth models. All the data are presented in Suppl. Table 1 to Suppl. Table 6. Suppl. Table 2 contains data from Levy et al., 2017.